The crystal structure of 5-amino-1-methyl-4-nitroimidazole, C4H6O2N4 - Cai Cao; Yumin Yan; Zhiwei Wen; Pengbao Lian; Jianlong Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C4H6O2N4, monoclinic, P2/c (no. 13), a = 14.6016(14) Å, b = 6.2077(6) Å, c = 12.9876(11) Å, β = 100.742(3)∘, V = 1156.60(19) Å3, Z = 8, Rgt(F) = 0.0656, wRref(F2) = 0.1524, T = 170 K .